Contents and Foreword of the INSANCITA Journal, Issue of August 2016 - Journal, Editor INSANCITA (ASPENSI, 2016)
INSANCITA journal will provide a peer-reviewed forum for the publication of thought-leadership articles, briefings, discussion, applied research, case and comparative studies, expert comment and analysis on the key issues surrounding the Islamic studies in general, not only in Indonesia but also in Southeast Asia and around the world, and its various aspects. Analysis will be practical and rigorous in nature. The INSANCITA journal, with Print ISSN 2443-2776, was firstly published on February 5, 2016, in the context to commemorate the Dies Natalies of HMI (Himpunan Mahasiswa Islam or Islamic Students Association) in Indonesia. The INSANCITA journal has been organized by the Alumni of HMI who work as Lecturers at the HEIs (Higher Education Institutions) in Indonesia; and published by Minda Masagi Press as a publisher owned by ASPENSI (the Association of Indonesian Scholars of History Education) in Bandung, West Java, Indonesia. The INSANCITA journal is published twice a year i.e. every February and August. All articles full text in PDF are free to be accessed and down load from the website at: www.mindamas-journals.com/index.php/insancitaBandung, Indonesia: August 30, 2016.Dr. Haji Berliana KartakusumahEditor-in-Chief of the INSANCITA Journal in Bandung; and a Senior Lecturer at the FKIP UNIDA (Faculty of Education and Teacher Training, University of Djuanda) in Ciawi, Bogor, West Java, Indonesia.Â